Mitigation of Peak to Average Power Ratio in Orthogonal Frequency Division Multiplexing through SOP-PTS - K. Srinivasa Rao (International Journal of Radio Frequency Innovations, 2023)
Orthogonal Frequency Division Multiplexing (OFDM) is a popular multicarrier modulation technology extensively employed in 4G wireless communication systems to transmit data over a dispersive channel. To address the Peak-to-Average Power Ratio (PAPR) issue in OFDM, a technique called Partial Transmit Sequence (PTS) is commonly utilized. The PTS method involves dividing the data block into non-overlapping sub-blocks and then combining them using phase factors to mitigate PAPR. However, the conventional PTS approach encounters a challenge as the number of sub-blocks increases, leading to exponentially growing search complexity due to the need to explore all possible phase factor combinations. To overcome this complexity and effectively reduce PAPR, a novel approach is proposed in this study, known as Particle Swarm Optimization (PSO)-based PTS technique. PSO is a bio-inspired algorithm capable of efficiently searching the solution space to find optimal solutions. By employing PSO, the proposed PSO-PTS method achieves a significant reduction in computational complexity, particularly for large sub-blocks, while obtaining lower PAPR levels. The simulation results demonstrate that the PSO-PTS approach outperforms the conventional PTS method.
Keywords: OFDM; PAPR; PTS; Swam optimization algorithm; digital radio transmissions